2014
DOI: 10.1002/fsn3.112
|View full text |Cite
|
Sign up to set email alerts
|

Initial investigation of dietitian perception of plant‐based protein quality

Abstract: Interest in plant-based diets is increasing, evidenced by scientific and regulatory recommendations, including Dietary Guidelines for Americans. Dietitians provide guidance in dietary protein selection but little is known about how familiar dietitians are with the quality of plant versus animal proteins or methods for measuring protein quality. Likewise, there is a need to explore their beliefs related to dietary recommendations. The aim of this study was to assess dietitians' perceptions of plant-based protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
(13 reference statements)
0
10
1
3
Order By: Relevance
“…Interest in plant‐based diets has increased with the latest dietary recommendations to consume more vegetables and plant‐based foods high in protein such as soy . The protein digestibility‐corrected amino acid scores (the most widely recognized and approved method for evaluating protein quality) for soy protein are comparable with milk, meat and eggs making it the highest quality of all the plant proteins .…”
Section: Discussionmentioning
confidence: 99%
“…Interest in plant‐based diets has increased with the latest dietary recommendations to consume more vegetables and plant‐based foods high in protein such as soy . The protein digestibility‐corrected amino acid scores (the most widely recognized and approved method for evaluating protein quality) for soy protein are comparable with milk, meat and eggs making it the highest quality of all the plant proteins .…”
Section: Discussionmentioning
confidence: 99%
“…Peanut protein contains twenty amino acids and is a good source of arginine (USDA ). It is widely accepted that peanut protein, as a plant‐based food, is high in nutritional value and equivalent to meat and eggs for human growth and health (Hughes et al ., ). Since it was reported that peanut protein has good functional properties such as emulsifying capability, emulsion stability, foaming capacity (FC), excellent water retention and high solubility (Zhao et al ., ,b).…”
Section: Introductionmentioning
confidence: 97%
“…In topic 2, 3 questions (3)(4)(5) were considered that assess knowledge about the risks and benefits associated with vegetarian diets. Topic 3 grouped 8 questions (17)(18)(19)(20)(21)(22)(23)(24) on the knowledge of the critical and specific nutrients of the said diets. Finally, topic 4 considered aspects such as the adoption of vegetarian diets in different stages of life, and these aspects were considered in 11 questions (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Knowledge Questionnairementioning
confidence: 99%